Étude des saponines isolées d'une espèce d'holothurie de la lagune de Bizerte - LOUIZ, Ibtissem; SELLEM, F.; TEKITEK, A.; LANGAR, Habib; EL ABED, Amor (INSTM Bulletin : Marine and Freshwater Sciences, 2003)
Following a separation by thin layer chromatography we demonstrate the presence of several types of saponins in partially purified extracts of Holothuria tubulosa of the Bizerte lagoon. These compounds appear quantitatively different according to the sexual period. Saponins of Holothuria tubulosa present an important hemolytic activity.